Functions and strategies for enhancing zinc availability in plants for sustainable agriculture - Hamzah Saleem, Muhammad; Usman, Kamal; Rizwan, Muhammad; Al Jabri, Hareb; Alsafran, Mohammed (Frontiers in Plant Science, 2022)
Zinc (Zn), which is regarded as a crucial micronutrient for plants, and is considered to be a vital micronutrient for plants. Zn has a significant role in the biochemistry and metabolism of plants owing to its significance and toxicity for biological systems at specific Zn concentrations, i.e., insufficient or harmful above the optimal range. It contributes to several cellular and physiological activities of plants and promotes plant growth, development, and yield. Zn is an important structural, enzymatic, and regulatory component of many proteins and enzymes. Consequently, it is essential to understand the interplay and chemistry of Zn in soil, its absorption, transport, and the response of plants to Zn deficiency, as well as to develop sustainable strategies for Zn deficiency in plants. Zn deficiency appears to be a widespread and prevalent issue in crops across the world, resulting in severe production losses that compromise nutritional quality. Considering this, enhancing Zn usage efficiency is the most effective strategy, which entails improving the architecture of the root system, absorption of Zn complexes by organic acids, and Zn uptake and translocation mechanisms in plants. Here, we provide an overview of various biotechnological techniques to improve Zn utilization efficiency and ensure the quality of crop. In light of the current status, an effort has been made to further dissect the absorption, transport, assimilation, function, deficiency, and toxicity symptoms caused by Zn in plants. As a result, we have described the potential information on diverse solutions, such as root structure alteration, the use of biostimulators, and nanomaterials, that may be used efficiently for Zn uptake, thereby assuring sustainable agriculture.